Barriers and Enablers to Participation in Higher Education: An Exploratory Study: Muhammad Awab-us-Sibtain ، Ahmed Usman ، Baqir Husnain (PJDOL, 2023)
This article draws from narratives of 14 slum dwellers of Christian Colony, Islamabad, Pakistan, to explore their struggle through a web of barriers and enablers to participate in higher education. Using the qualitative approach, primary data was collected through in-depth interviews. The respondents were mostly from the families where males worked as sanitary workers or unskilled laborers while the females worked as sanitary workers or housemaids. The interview data was transcribed, labelled and thematically analyzed. tion of the slum dwellers in higher education.Keywords: higher education; m